Noise Traders? Trigger Rates, FX Options, and Smiles - Christian Pierdzioch (Kiel Institute of World Economics (IfW), 2000)
A contingent claims valuation model which allows to highlight the implications of program trading in spot markets for the pricing of European-style foreign currency options and for the volatility strike structure implicit in these contracts is devoloped. The curvature of the volatility strike structure is explained by focusing attention on the expected aggregate net volume and direction of standing orders executed when the exchange rate reaches certain implicit price barriers triggering program traders to reallocate financial wealth. The valuation framework allows to endogenously reproduce the characteristic convex shape of volatility strike structures documented in the empirical literature. A volatility-based test for implicit price barriers in foreign exchange markets is employed to examine whether empirical evidence supports the barriers hypothesis of the volatility strike structure proposed in the paper.
Keywords: G13; F31; 330; Foreign Currency Options; Volatility Smile; Noise Trading; Implicit Price Barriers; GARCH model; Devisenoptionsgeschäft; Optionspreistheorie; Noise Trading; Wechselkurs; Volatilität; Stochastischer Prozess; Devisenhandel; Mikrostrukturanalyse; Schätzung; Theorie; Deutschland; Vereinigte Staaten; Japan; Großbritannien; Kanada